DELIVERY STRATEGY AND MARKETING COMMUNICATION OF TOURISM SERVICES (TOURISM DESTINATION STUDY MUARO JAMBI TEMPLE) - ERIDA ERIDA; YENNY YUNIARTI; RAJA SARAH FATRICIA (Journal of Business Studies and Management Review, 2018)
This study aims: 1). Analyzing consumer perceptions of marketing delivery strategy and marketing communication services run on the object of Muarojambi temple, 2). Analyzing the influence of delivery strategy and communication of tourism service pemsasaran to the tourists interest to visit Muarajambi temple. 3). Recommends marketing delivery strategy and marketing communication services that can be applied in increasing interest and tourist visit to Muarojambi temple. The sample used is the community / tourists who numbered 110 respondents. Analyzer used average score to know perception of society, and multiple linear regression analysis. The results showed that the community / tourists give a positive response to the marketing delivery strategy and communication of tourism destinations Muara Jambi temple. From the results of hypothesis testing, there are significant influence both simultaneously and partially variable delivery strategy and marketing communications to the interests of tourist visits. It should be increased the frequency of attractions, cultural titles / festivals as one of the keys to successfully bringing tourists in Muarajambi, besides the support of other physical facilities. It takes the involvement of all stakeholders in the development of tourism potential and promotion through the choice of effective marketing communication strategy of tourism services to reach the wider market through the utilization of social media / internet, in addition to direct promotion through exhibition and tourism expo